Association of Serum Programmed Cell Death Protein 1 (PD-1) and Gene Polymorphism with Some Valid Predictors for Systemic Lupus Erythematosus (SLE) Patients in Basra Province, Iraq - Alsalimi, Sadoun Abbas; Al-Fartosy, Adnan Jassim Mohammed (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: Systemic Lupus Erythematosus (SLE) is a systematic autoimmune disorder characterized by the production of autoantibodies against nuclear antigens and inflammation initiation. We aimed to examine the correlation between IL-18, IL-37, and PD-1, and the potential link between polymorphisms in the PD-1 gene located in intron-4 and the susceptibility to SLE. MATERIALS AND METHODS: This cross-sectional study included 43 SLE and 53 healthy individuals. Blood samples were obtained and underwent biochemical examination. The polymorphisms were screened by amplifying the intron-4 of the PD-1 gene using particular primers and then verified through sequencing. RESULTS: Our findings demonstrated statistically significant positive correlations between IL-18, IL-37, and PD-1, while the AUC of the ROC curve is 0.985, 0.968, and 0.940, and cut-off concentration is ≥132.87, ≥62.98, and ≥169.02, respectively. Moreover, two separate SNPs (rs6705653 and rs41386349) were discovered within intron-4 of the PD-1 gene. The genotype AA of the +7499 (G/A) SNP was significantly related with an increased risk of SLE (OR=3.11, 95%CI=1.52–5.94, p-value=0.031). Additionally, the A allele was identified as a risk allele (OR=1.59, 95%CI=1.09–2.31, p-value=0.043). Nevertheless, our study didn’t find any noteworthy connection between the allele and genotype of the +7209 (C/T) polymorphism region of the PD-1 gene frequencies and the susceptibility to SLE. CONCLUSION: IL-18, IL-37, and PD-1 may play significant roles in SLE immune responses and processes. Furthermore, the sequencing examination of intron-4 within the PD-1 gene demonstrated a noteworthy correlation between the A allele and the AA genotypes of PD-1 +7499 (G/A) SNP presence with the increased SLE susceptibility.